The role of smallholder generation from agriculture in sub-saharan Africa - Delgado, Christopher L. (International Food Policy Research Institute, 1997)
What insights for Southern Africa can be gained from studying the income-generating decisions of small farmers both there and in the rest of Sub-Saharan Africa? Much research has been conducted over the past three decades on how and why African smallholders diversity their income from sources outside of farming. Although pressure on the land has been less of an issue in West and Central Africa than in the highlands of East Africa and parts of Southern Africa, experiences throughout the region suggest that incorporating rural Africans into a sustained process of income growth is a much more complex issue than land reform alone.